Las mujeres en las cadenas de suministro agrícola y los sistemas alimentarios: Fomento de la inversión con perspectiva de género - Howland, Fanny; Derenoncourt, Ena (2023)
The presentation is about women in the agricultural value chain and their financial inclusion. It focuses on the gender gaps for the financial inclusion of women in value chains and on successful cases and tools for women's financial inclusion.